Catasthropic Health Expenditure Analysis Based on Cataracts Severity at Public & Private Hospital in Surabaya - Putri, Linta Meyla; Rochmah, Thinni Nurul; Ernawaty, Ernawaty (Journal of Health Management Research, 2022)
Background: The rate of visual disorders due to cataracts in Indonesia is the highest in Southeast Asia region and got the third place in the world at 1.47%. The prevalence of cataracts in East Java Province based on Riskesdas 2013 was 1.6%. Every year as many as 38 thousand residents of East Java Province are threatened with cataracts. Cataracts require a very large cost for medication. Aims: This study aims to conduct a Health Expenditure Analysis of cataract patients at Public and Private Hospital in Surabaya. Methods: Observational analytical research using quantitative methods. The time approach used for this research is a prospective design. The sample in this study were 174 patients. Results: Based on the results of the study, there was a significant difference (p-value = 0.001) between the Health Expenditure of cataract patients in private hospitals and government hospitals. The average health expenditure at private eye hospitals was higher than that of government eye hospitals, with an average difference -an average of IDR 4,240,030 per patient. Even so, patients from private and government hospitals experienced catastrophic health expenditure. Based on the chi-square test, there was a significant relationship between cataract severity (p-value¬= 0.001) and the incidence of catastrophic health expenditure. Conclusion: Catasthropic health expenditure can be experienced by patients in both private and public hospitals due to health costs incurred for cataract treatment for a period of 3 months.